Magnetic domains in H-mediated Zn0.9Co0.1O microdisk arrays. Issue 62 (14th June 2016) - Kim, Won-Kyung; Cheon, Miyeon; Lee, Seunghun; Lee, Tae-Woo; Park, Jung Jin; Cho, Chae Ryong; Park, Chul Hong; Takeuchi, Ichiro; Jeong, Se-Young
Abstract : We have fabricated and studied magnetic domains in the periodic ZnCoO microdisk structures at room temperature with MFM technique. The z-component of the remanent magnetic moment is uniform even though the value is much smaller than the saturation magnetic moment. Abstract : In this study, we have fabricated and studied magnetic domains in the periodic H-mediated Zn0.9 Co0.1 O (H-ZCO) microdisk structures at room temperature with the MFM technique. The results of MFM show that the z-component of the remanent magnetic moment is uniform even though the value is much smaller than that of the saturation magnetic moment. In the investigation of H-ZCO microdisk arrays in different volumes, the magnetic domains observed on different sizes of the H-ZCO microdisks exhibited the same magnetic domain characteristics, perpendicular magnetization, regardless of the volume. Also, we confirmed that the ferromagnetism in the H-ZnCoO system is mediated by hydrogens with the MFM results of ZnCoO hydrogen injected and dehydrogenated.